An examination of the dynamics of happiness using vector autoregressions - Martin Binder; Alex Coad (Max Planck Institute of Economics, 2009)
We use a panel vector autoregressions model to examine the coevolution of changes in happiness and changes in income, health, marital status as well as employment status for the British Household Panel Survey (BHPS) data set. This technique allows us to simultaneously analyze the impact of the aforementioned factors on each other. We find that increases in happiness are associated with subsequent increases in income, marriage, employment, and health variables, while increases in the these life-domain variables (except health) tend to be followed by decreases in happiness in subsequent periods, suggesting adaptation dynamics in all domains. These findings are quite robust to different model specifications.
Keywords: I31; D63; C33; 330; Happiness dynamics; vector autoregressions; subjective well-being; BHPS